Analisis Pendekatan Pembelajaran Pendidikan Agama Islam Dalam Kurikulum Merdeka - Huwaida Huwaida (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This study discusses the learning approach in the independent curriculum applied in Islamic Religious Education (PAI) learning as stated in the Decree of the Director General of Islamic Education Number 3211 of 2022 concerning the Learning Achievements of Islamic Religious Education and Arabic Language in the Independent Curriculum in Madrasahs and in the Islamic Religious Education and Character Education Teacher Guidebook for Senior High Schools/Vocational High Schools Class X. This study aims to provide a comprehensive analysis of various approaches in PAI learning that are in accordance with the Independent Curriculum in Indonesia. A qualitative analysis approach was implemented, which involved extensive library research conducted to review existing literature related to learning approaches and PAI subject in the Independent Curriculum. The data used are secondary data from various existing scientific literature. The results of the study indicate that the learning approaches applied are Student-Centered Learning, Inquiry and Discovery Learning, Problem Based Learning, Project Based Learning and Collaborative Learning